Análisis socioeconómico del sector educativo público en el Presupuesto General del Estado - Mosquera Véliz, Leonel Salvatore (2022)
Education is undoubtedly one of the most prevailing and necessary services to achieve the economic growth and development of peoples. Indeed, developed countries have greatly enhanced the education and knowledge of their citizens, finding in it the engine of their wealth. Now, any service that wants to have the level of good sense and responsibility must be planned and structured. Thus, the Education Service must have excellent planning, administration and management accompanied by a budget according to the quality and warmth that it wishes to provide. On the other hand, the budget that is executed in education should always be considered as an investment, since it is through Science that nations have grown and will grow. However, although it seems contradictory, on more than one occasion this investment ends up being considered an expense understood as a loss. Can the investment turn into a loss?........